Telaah Pengalaman Intrapreneurial Pada Bisnis E-Commerce Diario: Sebuah Studi Kualitatif - Dini Indiani; Margo Purnomo; Ratih Purbasari (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The aim of this research is to analyze intrapreneurial experience on the e-commerce business "Diario". The research design employs a qualitative method with observation and conducting interviews with key informants, specifically the Manager of the Diario brand. The research data obtained from the interviews were analyzed using narrative analysis techniques, as it describes stories or ideas communicated to all relevant stakeholders. The findings of this study reveal nine intrapreneurial experiences that have an impact on the Diario e-commerce business. Another finding shows that overall, intrapreneurial experience can help e-commerce businesses develop the innovation as well as create a better and more motivated working environment for employees. The limitations of this study are that it only analyzes one e-commerce business and uses only interviews as the data collection method. For future research, a comparative analysis can be conducted on several other similar e-commerce businesses to obtain more varied results.